Pengaruh Penggunaan Model Pembelajaram Problem Based Learning dan Motivasi Terhadap Hasil Belajar Siswa - Moslimah (Jurnal Ilmiah Edukatif, 2023)
It will be difficult for students learning outcomes in fiqh subjects to improve if the learning methods used still use the old (conventional) methods; this does not mean that conventional ones cannot be used; it just means that students need a new atmosphere in receiving the material, to maximize learning outcomes researchers use Problem-Based Learning or learning problem-based is a teaching model characterized by real problems as a context for students to learn critical thinking and problem-solving skills and gain knowledge. Research objectives: analyze the effect of using the PBL learning model and motivation on student learning outcomes in the Fiqh subject, analyze the influence of using the PBL learning model on the learning outcomes of students in the Fiqh subject, and (3) analyze the impact of motivation on student learning outcomes in the Fiqh subject. The research method used in this research is a quantitative method with a descriptive type. Data collection techniques use observation, documents, and questionnaires. Primary data sources for students, while secondary data are journals, books, and documentation data at school. The results of this research, including the data analysis tests, state that using the PBL learning model and motivation has a positive and significant effect on student learning outcomes. The problem-based learning (PBL) learning model has a considerable influence on student learning outcomes. There is a substantial influence of motivation on student learning outcomes. Class VIII Fiqh subject at MTss Raudlatul Firdaus Kuburaya.